Retrospective reports of parental feeding practices and emotional eating in adulthood: The role of food preoccupation. (1st October 2016) - Tan, Cin Cin; Ruhl, Holly; Chow, Chong Man; Ellis, Lillian
Abstract: The current study examined the role of food preoccupation as a potential mediator of the associations between parental feeding behaviors during childhood (i.e., restriction for weight, restriction for health, emotion regulation) and emotional eating in adulthood. Participants (N = 97, Mage  = 20.3 years) recalled their parents' feeding behaviors during early and middle childhood and reported on current experiences of food preoccupation and emotional eating. Findings revealed that recalled parental feeding behaviors (restriction for weight, restriction for health, emotion regulation) and food preoccupation were positively associated with later emotional eating (correlations ranged from 0.21 to 0.55). In addition, recalled restriction for weight and emotion regulation feeding were positively associated with food preoccupation, r  = 0.23 and 0.38, respectively. Further, food preoccupation mediated the association between emotion regulation feeding and later emotional eating (CI95%  = 0.10 to 0.44). These findings indicate that parental feeding practices in childhood are related to food preoccupation, and that food preoccupation mediates the association between emotion regulation feeding in childhood and emotional eating in adulthood.